Accuracy of EMR-based algorithms for Adverse Event Detection - Southern, Danielle; Cheligeer, Cheligeer; Wu, Guosong; Eastwood, Cathy; Zeng, Yong; Boussat, Bastien; Flemons, Ward; Forster, Alan; Xu, Yuan; Quan, Hude (International Journal of Population Data Science, 2026)
Background Adverse events (AEs) are often measured using administrative data, which has validity limitations. Electronic Medical Records (EMRs) provide rich, unstructured data that can improve AE detection through data science methods. Objective: To evaluate the accuracy of EMR-based algorithms for AE detection and estimate AE prevalence. Methods We conducted a retrospective chart review validation study at a tertiary-care hospital (population 1.5M). Adult patients admitted between 2017–2022 with discharge summaries or narrative EMRs were included; only the most recent admission was analyzed. Seventeen algorithms were developed for specific AE categories and an overall “any AE” category using natural language processing (NLP) and machine learning. Prevalence, sensitivity, specificity, PPV, NPV, and model performance (AUC, accuracy, F1 score) were calculated using chart review as a reference. Results Of 10,939 charts, 10,659 were linked to discharge data; 2,069 patients had ≥1 AE. AE prevalence ranged from 0.2%–6.0%. Sensitivity and specificity varied (57%–100%, 74%–96%). For “any AE,” sensitivity was 63%, specificity 94%, PPV 72%, NPV 91%. Overall algorithm performance: AUC 78.4% (95% CI, 76.0–80.8), accuracy 87.6%, F1 score 67.2. Conclusion NLP-based algorithms applied to EMRs show strong performance despite low AE prevalence, offering a scalable approach to enhance AE surveillance and patient safety.